Electron Hopping between Fe 3 d States in Ethynylferrocene‐doped Poly(Methyl Methacrylate)‐poly(Decyl Methacrylate) Copolymer Membranes. Issue 4 (10th October 2017) - Cuartero, Maria; Acres, Robert G.; Jarolímová, Zdenka; Bakker, Eric; Crespo, Gaston A.; De Marco, Roland
Abstract: Synchrotron radiation‐valence band spectroscopy (SR‐VBS) has been utilized in a study of redox molecule valence states implicated in the electron hopping mechanism of ethynylferrocene in unplasticized poly(methyl methacrylate)‐poly(decyl methacrylate) [PMMA‐PDMA] membranes. In this communication, it is revealed that, at high concentrations of ethynylferrocene, there are observable Fe 3d valence states that are likely linked to electron hopping between ferrocene moieties of neighbouring redox molecules. Furthermore, electrochemically induced stratification of ethynylferrocene in an oxidized PMMA‐PDMA membrane produces a gradient of Fe 3d states toward the buried interface at the glassy carbon/PMMA‐PDMA membrane enabling electron hopping and electrochemical reactivity of dissolved ethynylferrocene across this buried film. Abstract :